Nutritional Assessment of Nursing Home Resident in Baghdad City - Mohammed F. Khalifa; Murtada K. AL-Jebory (Kufa Journal for Nursing Sciences)
Objectives: The objective of the study is to determine the nutritional status of elderly resident in nursing home through anthropometric measurements (Body Mass Index, mid-upper arm circumference) dietary pattern and food intake and clinical appearance in Baghdad city.